Hypertension, chronic obstructive pulmonary disease, diabetes and depression among older methadone maintenance patients in British Columbia. (11th March 2013) - Maruyama, Anna; Macdonald, Scott; Borycki, Elizabeth; Zhao, Jinhui
Abstract Introduction and Aims Risk factors in older methadone maintenance treatment (MMT) patients may put them at a greater risk of acquiring chronic diseases; however, this group might experience barriers to treatment resulting in reduced recommended prescriptions. The research objective for this study was to assess whether MMT patients were significantly different from a matched control group in terms of medications dispensed for hypertension, chronic obstructive pulmonary disease (COPD), diabetes and depression. Design and Methods The research design was a case‐control study, where prescription claims data from the British Columbia database were used. MMT patients 50 years of age and older were randomly selected, and control subjects were individually matched in terms of age, sex, social assistance coverage and geographic jurisdiction. Results Each group consisted of 199 participants. Odds ratios (OR) were calculated to compare the odds of MMT patients to non‐MMT patients on a first‐line medication for each chronic disease under investigation. The MMT group was significantly more likely to receive medications for COPD (OR = 32.68, P < 0.001) and depression (OR = 4.07, P < 0.001), and no significant differences for hypertension (OR = 0.86) or diabetes (OR = 0.74). Discussion Higher rates of COPD among MMT clients is likely explained by elevated smoking, and higher rates of depression may be explained by multiple disadvantages associated with substance use. Although the groups were similar for diabetes prescriptions, the MMT group likely experienced barriers to receiving treatment since prior research suggests their rates should be elevated due to methadone use. [Maruyama A, Macdonald S, Borycki E, Zhao J. Hypertension, chronic obstructive pulmonary disease, diabetes and depression among older methadone maintenance patients in British Columbia. Drug Alcohol Rev 2013;32:412–418]